1999
DOI: 10.1080/00984109909350175
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Immunoassays for Predicting the Toxicity of Malathion in a Laboratory Fish Model

Abstract: This study describes the use of a panel of immune assays, originally developed by the National Toxicology Program for assessing xenobiotic-induced immunotoxicity in mice, to quantify the effects of sublethal malathion exposure on the immune responses of fish. For this study, Japanese medaka (Oryzias latipes) were exposed subchronically to the organophosphate pesticide malathion in a series of two experiments. In the first set of studies, fish were exposed for 7 or 14 d to untreated well water (i.e., controls) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…There are many animal studies showing the toxic effect of malathion on the kidney due to oxidative stress and negative alterations on antioxidant enzyme activities,12–20 leading to reduced total kidney cell numbers,21 histological and functional impairment of renal tubules,22–25 glomerular inflammation26 and proteinuria 25 26…”
Section: Discussionmentioning
confidence: 99%
“…There are many animal studies showing the toxic effect of malathion on the kidney due to oxidative stress and negative alterations on antioxidant enzyme activities,12–20 leading to reduced total kidney cell numbers,21 histological and functional impairment of renal tubules,22–25 glomerular inflammation26 and proteinuria 25 26…”
Section: Discussionmentioning
confidence: 99%
“…6 -8 (ii) Malathion reduced host resistance against Yersinia infection in fish, 9 attenuated antigen-induced antibody response 9 and suppressed splenic plaqueforming cells in mice and rats. 10 However, some studies have shown that malathion either caused immunopotentiation or did not affect immunity in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Many times the recommended therapy in the parasite infestation combat is based on chemical products use, especially the organo-phosphates (Rao & Dad, 1979). However, it is known that the organophosphate used for the disease treatments can also cause histopathologic changes in many fish organs but studies in this area are still in an incipient phase (Ram et al, 1989;Hamm et al, 1998;Beaman et al, 1999). The aim of this bioassay was to investigate the histopathologic changes on the kidney of Prochilodus lineatus exposed to a high Dipterex 500 (Trichlorfon) concentration.…”
Section: Introductionmentioning
confidence: 99%